First clinical use of novel ablation catheter incorporating local impedance data. (19th June 2018) - Martin, Claire A.; Martin, Ruairidh; Gajendragadkar, Parag R.; Maury, Philippe; Takigawa, Masateru; Cheniti, Ghassen; Frontera, Antonio; Kitamura, Takeshi; Duchateau, Josselin; Vlachos, Konstantinos; Bourier, Felix; Lam, Anna; et al.
Abstract: Introduction: Successful catheter ablation is limited by both poor spatial resolution of abnormal local signals and inability to deliver an effective lesion due to poor tissue contact. We report first worldwide use of the Intellanav MiFi OI catheter (Boston Scientific), providing ultra‐high density mapping and incorporating a "DirectSense" algorithm to measure local tissue impedance (LI). Methods and results: 31 patients (65±6 years, 20 male) underwent ablation. LI from the catheter, generator impedance (GI) and maximum electrogram amplitude were recorded in the blood pool, and in regions from healthy to dense scar before, during and after ablation. The catheter demonstrated clear nearfield signal where standard bipolar recordings included farfield signal. LI was lower in dense scar than either healthy tissue or blood pool, and demonstrated an exponential relationship with maximum electrogram amplitude. Maximum LI drop on ablation linearly correlated with initial LI. The median LI drop for successful lesions, resulting in lack of local tissue capture, was 16.0Ω (12.1–19.8 Ω) for LV and 14.6 Ω (10.0–18.3 Ω) for LA, which was larger than for unsuccessful lesions (LV: 9.4 Ω [5.4–15.6 Ω] P = 0.001; LA: 6.8 Ω [4.7–13.0 Ω], P = 0.049). LI percentage drop was also significantly larger for successful than unsuccessful lesions (LV: 17.1 Ω [14.0–19.6 Ω] vs. 10.6 Ω (7.1–16.5 Ω) P = 0.002; LA: 14.2 Ω [10.8‐19.5 Ω] vs. 7.5Ω [5.1–11.0 Ω], P = 0.005). Conclusion: This novel catheter gives reproducible recordings of local impedance, which are dependent on scar level. Absolute LI drop, and also percentage drop, on ablation may give an indication of tissue contact and subsequent effective lesion formation.